Prospects and Challenges of Graphene in Biomedical Applications1. (13th March 2013) - Bitounis, Dimitrios; Ali‐Boucetta, Hanene; Hong, Byung Hee; Min, Dal‐Hee; Kostarelos, Kostas
Abstract Graphene materials have entered a phase of maturity in their development that is characterized by their explorative utilization in various types of applications and fields from electronics to biomedicine. Herein, we describe the recent advances made with graphene‐related materials in the biomedical field and the challenges facing these exciting new tools both in terms of biological activity and toxicological profiling in vitro and in vivo. Graphene materials today have mainly been explored as components of biosensors and for construction of matrices in tissue engineering. Their antimicrobial activity and their capacity to act as drug delivery platforms have also been reported, however, not as coherently. This report will attempt to offer some perspective as to which areas of biomedical applications can expect graphene‐related materials to constitute a tool offering improved functionality and previously unavailable options.